A Debreceni m. kir. Tudományegyetem első rektora: Kiss Ferenc (1862–1948) - Virágos, Márta (Gerundium, 2010)
Professor Ferenc Kiss Was the First Rector of the Hungarian Royal University of Arts and Sciences in Debrecen.Through delving into the relevant biographical data and publishing his salutatory oration of 1914, the author recalls reminiscences of Ferenc Kiss, the outstanding professor of theology, who was the first rector of the one-time University of Debrecen.